Improved Calcium Scoring at Dual-Energy Computed Tomography Angiography Using a High-Z Contrast Element and Novel Material Separation Technique. Issue 3 (May 2018) - Lambert, Jack W.; Sun, Yuxin; Ordovas, Karen G.; Gould, Robert G.; Wang, Sizhe; Yeh, Benjamin M.
Abstract : Objectives: The aim of this study was to compare the accuracy of existing dual-energy computed tomography (CT) angiography coronary artery calcium scoring methods to those obtained using an experimental tungsten-based contrast material and a recently described contrast material extraction process (CMEP). Methods: Phantom coronary arteries of varied diameters, with different densities and arcs of simulated calcified plaque, were sequentially filled with water, iodine, and tungsten contrast materials and scanned within a thorax phantom at rapid-kVp-switching dual-energy CT. Calcium and contrast density images were obtained by material decomposition (MD) and CMEP. Relative calcium scoring errors among the 4 reconstructed datasets were compared with a ground truth, 120-kVp dataset. Results: Compared with the 120-kVp dataset, tungsten CMEP showed a significantly lower mean absolute error in calcium score (6.2%, P < 0.001) than iodine CMEP, tungsten MD, and iodine MD (9.9%, 15.7%, and 40.8%, respectively). Conclusions: Novel contrast elements and material separation techniques offer improved coronary artery calcium scoring accuracy and show potential to improve the use of dual-energy CT angiography in a clinical setting.